How does your prairie (re)grow?: Interactions of seed additions with resource availability, heterogeneity, and disturbance on recruitment and diversity in a restored tallgrass prairie - Stanton, Nicole Lynn (Kansas State University, 2014)
Temperate grasslands are among the most threatened biomes in the world, with the largest historical losses due to conversion to agricultural land. While much of this biome has already been converted, there is concern the last remaining remnants in North America will be converted in response to increasing demand for crops used for ethanol production. Thus, restoring grasslands post-anthropogenic disturbance is increasingly important for conserving grassland biodiversity. Two major challenges for prairie restorations are establishing the many subdominant and rarer species found in native prairie, and offsetting the typical decline in richness and diversity over time as restorations age. Repeated seed addition of targeted species is commonly used to override low and declining plant richness and diversity. While this is generally effective early in restoration (i.e., as communities are establishing), its effectiveness in later stages (i.e., when established communities are often losing diversity) remains unknown. I investigated plant community responses to combinations of resource manipulations and disturbances coupled with a seed addition in a 15-yr old restored grassland to test the hypothesis that spatial resource heterogeneity increases the rate of colonization into established prairie restoration communities. Seeds were added to a long-term restoration experiment involving soil depth manipulations (deep, shallow) crossed with nutrient manipulations (reduced N, ambient N, enriched N). Seedling emergence was generally low and only 8 of the 14 forb species added were detected in the first growing season. I found no effect of increased resource heterogeneity on the abundance or richness of seedlings. There was a significant nutrient effect (p<0.1, α=0.1) on seedling abundance, with higher emergence in the enriched N than the ambient N treatment. I also found unexpected nutrient effects on richness, diversity and Mean C (Mean C = Σ CoCi*Ai, where CoC=Coefficient of Conservatism and A=relative abundance of the ith species). All values, except Mean C, were higher in the enriched N treatment than in either the reduced or ambient N treatments. Mean C was lowest in the enriched N treatment, and highest in the whole-plot control, suggesting that the majority of species contributing to higher richness and diversity in the enriched N treatment were “weedier” species. In a separate experiment, I found no effect of small-scale disturbances (aboveground biomass removal or soil disturbance) on seedling abundance or seedling richness. I did find a marginal effect of disturbance type on seedling richness (p=0.11, α=0.1), with higher seedling richness in the soil disturbance than the aboveground biomass removal treatment. I did not find any disturbance effects on community response variables. These results indicate that recruitment from seed additions into well-established restored communities is relatively low in the first year following a seed addition, regardless of resource availability and heterogeneity. Follow-up studies to determine recruitment rates in subsequent years are needed to elucidate whether recruitment responses are driven more by individual species differences or by environmental mechanisms.
Keywords: Tallgrass prairie; Ecological restoration; Resource availability and heterogeneity; Long-term; Propagule; Seedling; Ecology (0329)